2023
DOI: 10.3390/vetsci10010036
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Oral Florfenicol Medication and Residues on the Kidney and Liver of Nile Tilapia Oreochromis niloticus (L.)

Abstract: Florfenicol (FFC), an approved aquaculture antibiotic, is administered in feed at doses of 10–15 mg kg biomass−1 day−1 for 10 successive days. In this study, healthy Oreochromis niloticus were fed with 0–10 times the therapeutic dose of 15 mg kg biomass−1 day−1 for 10 days and tracked for 43 days post dosing. Assessments of residue accrual and depletion, oxidative stress, serum biochemistry, histopathology and extent of kidney and liver damages were made. FFC dosing reduced the feed intake significantly. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This was the main reason for including the higher dose of FFC in the study. Previous safety studies conducted in tropical conditions have shown various alterations in the kidney and liver tissues of Nile tilapia (Oreochromis niloticus) in response to oral FFC [44].…”
Section: Discussionmentioning
confidence: 99%
“…This was the main reason for including the higher dose of FFC in the study. Previous safety studies conducted in tropical conditions have shown various alterations in the kidney and liver tissues of Nile tilapia (Oreochromis niloticus) in response to oral FFC [44].…”
Section: Discussionmentioning
confidence: 99%
“…At high concentrations, several metallic nanoparticles are toxic, killing fish [49]. Growth inhibition was also reported in Cyprinus carpio by copper nanoparticles after thirty days of exposure [82]. Similarly, dose-dependent reduced feed intake and fish mortality have been associated with oral administration of some antibiotics [83].…”
Section: Discussionmentioning
confidence: 98%
“…This heavy metal can further stress the liver, exacerbating cellular damage [36,37]. A compromised liver poses a serious threat to the overall health and survival of O. niloticus, impacting individual fitness and potentially affecting entire populations [38]. ON the other hand, during warmer months, fish require more energy, pushing their metabolic machinery to its limits [39].…”
Section: Discussionmentioning
confidence: 99%